Macrobrachium rosenbergii Genome Editing Breeding with CRISPR–Cas Nucleases, Base Editors, and Prime Editors - Guo Li; Xinzhi Zhou; Guanglin Zhu; Yingjia Pan; Junjun Yan; Jilun Meng; Tiantian Ye; Yaxian Cheng; Cui Liu; Zhimin Gu (Animals)
This review focuses on CRISPR genome editing technology, particularly its application in the study of Macrobrachium rosenbergii (M. rosenbergii). It first elaborates on the basic principles and mechanisms of CRISPR–Cas9 technology, base editors, and prime editors. Then, it explores the application of this technology in M. rosenbergii breeding, including improving growth rate, enhancing disease resistance, and sex control. Additionally, it introduces the progress of genome editing technology in M. rosenbergii, epidemiology and pathogenesis, diagnostic techniques, analyzes the opportunities and challenges it faces, reviews the historical evolution, and looks ahead to future development directions. CRISPR technology has brought new opportunities to the research and industrial development of M. rosenbergii, but it also needs to address numerous technical and safety challenges.